# Solve for k -2/3k+3/7=1/2 -23k+37=12
Simplify each term.
Combine k and 23.
-k⋅23+37=12
Move 2 to the left of k.
-2k3+37=12
-2k3+37=12
Move all terms not containing k to the right side of the equation.
Subtract 37 from both sides of the equation.
-2k3=12-37
To write 12 as a fraction with a common denominator, multiply by 77.
-2k3=12⋅77-37
To write -37 as a fraction with a common denominator, multiply by 22.
-2k3=12⋅77-37⋅22
Write each expression with a common denominator of 14, by multiplying each by an appropriate factor of 1.
Multiply 12 and 77.
-2k3=72⋅7-37⋅22
Multiply 2 by 7.
-2k3=714-37⋅22
Multiply 37 and 22.
-2k3=714-3⋅27⋅2
Multiply 7 by 2.
-2k3=714-3⋅214
-2k3=714-3⋅214
Combine the numerators over the common denominator.
-2k3=7-3⋅214
Simplify the numerator.
Multiply -3 by 2.
-2k3=7-614
Subtract 6 from 7.
-2k3=114
-2k3=114
-2k3=114
Multiply both sides of the equation by -32.
-32⋅(-2k3)=-32⋅114
Simplify both sides of the equation.
Simplify -32⋅(-2k3).
Cancel the common factor of 3.
Move the leading negative in -32 into the numerator.
-32⋅(-2k3)=-32⋅114
Move the leading negative in -2k3 into the numerator.
-32⋅-2k3=-32⋅114
Factor 3 out of -3.
3(-1)2⋅-2k3=-32⋅114
Cancel the common factor.
3⋅-12⋅-2k3=-32⋅114
Rewrite the expression.
-12⋅(-2k)=-32⋅114
-12⋅(-2k)=-32⋅114
Cancel the common factor of 2.
Factor 2 out of -2k.
-12⋅(2(-k))=-32⋅114
Cancel the common factor.
-12⋅(2(-k))=-32⋅114
Rewrite the expression.
-1⋅(-k)=-32⋅114
-1⋅(-k)=-32⋅114
Multiply.
Multiply -1 by -1.
1⋅k=-32⋅114
Multiply k by 1.
k=-32⋅114
k=-32⋅114
k=-32⋅114
Multiply -32⋅114.
Multiply 114 and 32.
k=-314⋅2
Multiply 14 by 2.
k=-328
k=-328
k=-328
The result can be shown in multiple forms.
Exact Form:
k=-328
Decimal Form:
k=-0.10714285…
Solve for k -2/3k+3/7=1/2

## Our Professionals ### Robert Kristofer ### Anna Frok ### Magnus Flores ### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top